Peer Feedback Reflects the Mindset and Academic Motivation of Learners - Zhang, Junfeng; Kuusisto, Elina; Nokelainen, Petri; Tirri, Kirsi (Frontiers in Psychology, 2020)
Given that little is known how peer feedback reflects adolescents’ academic well-being in different cultures, this study investigates, by means of multiple-group structural equation modelling (SEM), the influence of peer feedback on the mindset and academic motivation of Chinese (N=992) and Finnish (N=870) students in the fourth to the ninth school grades. Within this investigation, we also explore the culture-invariant and culture-dependent nature of student feedback, mindset and academic motivation. The results indicate that the way students praise their peers in their feedback primes and modifies their mindsets and academic motivation. Person-focused praise reflects a fixed mindset and negative academic motivation (i.e. avoidance), whereas process-focused praise undermines negative academic motivation. The pupils in the two samples had growth mindsets. However, the Finnish students preferred to bestow neutral praise and to be more negative with regard to their academic motivation whereas the Chinese students favoured process- and person-focused praise, the former reflecting not only their growth mindset but also their positive academic motivation (i.e. trying).